2018
DOI: 10.1107/s2053230x18010439
|View full text |Cite
|
Sign up to set email alerts
|

TssA from Aeromonas hydrophila: expression, purification and crystallographic studies

Abstract: Crystals of different domain constructs of the TssA subunit from Aeromonas hydrophila have been crystallized in forms suitable for X-ray analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The structure of an Ah TssA2 A Nt2 domain construct (D231-L374) was solved to 1.76 Å with four subunits (chains A–D) in the asymmetric unit (Supplementary Table 6 ) arranged as two independent dimers, consistent with previous SEC analysis 33 , that showed that Ah TssA2 A Nt2 exists as dimers in solution. Each monomer folds into a cluster of seven α-helices (α1–α7), the arrangement of which is very similar to that of the EAEC TssA2 B Nt2 domain (RMSD = 2.0 Å) as determined by structural alignment 27 , 34 .…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The structure of an Ah TssA2 A Nt2 domain construct (D231-L374) was solved to 1.76 Å with four subunits (chains A–D) in the asymmetric unit (Supplementary Table 6 ) arranged as two independent dimers, consistent with previous SEC analysis 33 , that showed that Ah TssA2 A Nt2 exists as dimers in solution. Each monomer folds into a cluster of seven α-helices (α1–α7), the arrangement of which is very similar to that of the EAEC TssA2 B Nt2 domain (RMSD = 2.0 Å) as determined by structural alignment 27 , 34 .…”
Section: Resultssupporting
confidence: 81%
“…Expression and purification of His 6 .TssA2 A (1–478), His 6 .TssA2 A Nt2 (223–387), His 6 .TssA2 A Nt2-CTD (223–478) and TssA2 A CTD (381–478) was carried out as previously described 33 . Both MBP.TssA1 B CTD (303–373) and His 6 .TssA1 B Nt1 (1–255) were overexpressed and purified, with TssA1 B CTD (303–373) being separated from the MBP solubility tag by Factor Xa cleavage 51 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations